Semisolid Dosage - Daniels, Rolf; Lunter, Dominique (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Even in ancient times, semi-solid preparations for cutaneous application, popularly known as ointments, played an important role in human society. An advanced scientific investigation of "ointments" as dosage forms was initiated in the 1950s. It was only from then on that the intensive physico-chemical characterization of ointments as well as the inclusion of dermatological aspects led to a comprehensive understanding of the various interactions between the vehicle, the active ingredient and the skin. From then on, many researchers were involved in optimizing semi-solid formulations with respect to continuously changing therapeutic and patient needs. Aspects that have been dealt with were the optimization of dermato-biopharmaceutical properties and many different issues related to patient compliance, such as skin tolerance, applicability, and cosmetic appeal. Moreover, processing technology has been improved and analytical techniques were developed and refined in order to enable the improved characterization of the formulation itself as well as its interaction with the skin. This Special Issue serves to highlight and capture the contemporary progress and current research on semi-solid formulations as dermal drug delivery systems. We invite articles on all aspects of semi-solid formulations, highlighting the research currently undertaken to improve and better understand these complex drug delivery systems with respect to their formulation, processing and characterization issues.